COGNITIVE REAPPRAISAL AND MENTAL HEALTH PROBLEMS IN FEMALE UNIVERSITY TEACHERS DURING COVID-19: A MEDIATING ROLE OF EMOTIONAL EXHAUSTION - Sarah Pervez; Saleem, Sadia; Sayyeda Taskeen Zahra (Journal of Postgraduate Medical Institute, 2022)
Objective: To find out the role of emotional exhaustion as mediation in the association of cognitive reappraisal and mental health problems in female university teachers in COVID-19. Methodology: A correlational research design was utilized to get participants from different government and private universities of Lahore. Participants of this study were 100 university teachers having the ages of 25 to 60 years. Participants were selected using purposive sampling technique. Scales of Cognitive Reappraisal, Emotional Exhaustion, and Psychosocial Reactions of COVID-19 were utilized to get the data from the participants. Results: Findings of correlation analysis suggested interrelatedness of cognitive reappraisal, emotional exhaustion, and mental health problems. Additionally, mediation analysis suggested the significant mediating role of emotional exhaustion in the association of cognitive reappraisal and mental health issues. Conclusion: By identifying the risk and protective factors of mental health problems of working women at early stages, we can prevent them from adverse consequences of these issues.